Nesting Common Eider (Somateria mollissima) Population Quintuples in Northwest Greenland - Burnham, Kurt K.; Johnson, Jeff A.; Konkel, Bridger; Burnham, Jennifer L. (ARCTIC, 2012)
Common eider (Somateria mollissima) populations in Greenland severely declined throughout the 20th century. As a result, in 2001, harvest regulations were changed and the length of the hunting season was reduced. Recent data suggest that these changes have been successful, and population regrowth is occurring. In the Avanersuaq District, northwest Greenland, only one systematic survey quantifying the number of nesting eiders had previously been conducted, in 1997 and 1998. Although this district had historically been identified as having the largest number of breeding eiders in Greenland, the 1997–98 survey results showed a relatively small estimated population of 5000 pairs. However, it is not known to what extent changes in hunting regulations have affected nesting abundance in this area. Therefore, the Avanersuaq District was systematically resurveyed during the 2009 breeding season, approximately 11 years after the previous survey. These results showed that the population had increased to 5.4 times its 1997–98 size, with an annual compounded growth rate of 15.3%. On a single island, nearly 4500 active nests were observed. Five islands had more than 2600 nests each and comprised 75% of the total nests counted. Along with historical information to account for additional nesting habitat not surveyed, the observed population growth rate from this study suggests that the overall Avanersuaq common eider breeding population size ranges from 25 000 to 30 000 pairs, or roughly half of the total estimated West Greenland breeding population. Despite the significance of the Avanersuaq District as a breeding area for common eiders, we have only limited information about this population. The effects of recent extensions of the hunting season on this population are also unknown, and the only wintering location information is based on a few individuals banded in the 1920s and 1940s. Additional research on migratory movements is suggested before any further changes are made to hunting regulations. Au cours du XXe siècle, ...